The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1476-5381.1995.tb15143.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prejunctional 5‐HT receptors mediating inhibition of sympathetic vasopressor responses in the pithed rat

Abstract: 1 It has recently been shown that continuous infusions of 5-hydroxytryptamine (5-HT) are able to inhibit, in a dose-dependent manner, the pressor responses induced by preganglionic (T7-Tg) sympathetic stimulation in pithed rats pretreated with desipramine (50 mg kg- ', i.v.). This inhibitory effect, besides being significantly more pronounced at lower frequencies of stimulation (0.03-1 Hz) and devoid of tachyphylaxis, is reversible after interrupting the infusions of 5-HT (up to 5.6 pg kg-' min-'). In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 31 publications
(60 reference statements)
10
36
1
Order By: Relevance
“…Moreover, the potentiation of sympathetically-induced vasopressor responses after desipramine made it possible to reveal more marked sympatho-inhibitory responses to quinpirole at lower stimulation frequencies ( fig. 3), as previously shown for other agonists [15,17,18]. This inhibition by quinpirole is not because of tachyphylaxis, as the sympathetic responses remained unchanged in animals receiving saline ( fig.…”
Section: Systemic Haemodynamic Changessupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, the potentiation of sympathetically-induced vasopressor responses after desipramine made it possible to reveal more marked sympatho-inhibitory responses to quinpirole at lower stimulation frequencies ( fig. 3), as previously shown for other agonists [15,17,18]. This inhibition by quinpirole is not because of tachyphylaxis, as the sympathetic responses remained unchanged in animals receiving saline ( fig.…”
Section: Systemic Haemodynamic Changessupporting
confidence: 81%
“…4E), which are mainly mediated by a 1 -adrenoceptors [18]. Hence, haloperidol is not appropriate for analysing the pharmacological profile of receptors mediating sympatho-inhibition in our study, as similarly shown for other antagonists [18]. This attenuation by haloperidol could be due to blockade of vascular fig.…”
Section: Generalmentioning
confidence: 66%
See 2 more Smart Citations
“…11 Centrally administered 8-OH-DPAT, a 5-HT1A receptor agonist, has been shown to decrease blood pressure and sympathetic nerve activity. 12 The sites of 5-HT release in the periphery are the gut and intestines. 13 Both of these areas have minimal blood flow during exercise.…”
Section: Introductionmentioning
confidence: 99%